Accuracy assessment of orthophoto image surface model for as built survey data collection / Mohamad Azri Mohammed Noor - Mohammed Noor, Mohamad Azri (2022)
This study assess the accuracy obtainable from orthophoto surface model captured at different altitudes for positioning and two dimensional as built survey. To achieve this purpose, the objectives includes; perform data collection for as-built survey at different altitudes using the multi-rotor UAV; generate orthophoto image and surface model to extract position and 2D data; and compare the position and dimension between ground survey and orthophoto. Thus, the study focuses on producing positional and 2D data using orthophoto images captured at two different altitudes (50 and 120 meters) in order to evaluate which altitudes is more suitable for as build survey purpose. Once orthophotos generated, the position and 2D data were extracted and compared with field data using total station. The findings, concludes that orthophoto images could provide acceptable as-build accuracy with error at sub-meters level; and the lower the altitudes, the smaller error produced in both X and Y dimensions, area and in distance measured.